Evaluating corporate climate risk assessment results: Lessons learned from Taiwan’s top 100 enterprises - Chia-Chi Lee; Shih-Yun Kuo; Shih-Yu Lee; Huang-Hsiung Hsu; Kuei-Tien Chou; Tung-Li Mo; Chung-Pei Pien; Ya-Ting Kuo; En-Yu Chang; Kuan-Chun Huang; Ling-Ju Hsu; Yi-Meng Chao; et al. (Climate Risk Management)
In recent years, driven by the Task Force on Climate-related Financial Disclosures (TCFD), climate risk disclosure has developed as a key concrete action among the business community to address climate change. However, such disclosures are often incomplete or misleading, and improvements are needed both in terms of disclosure quantity and quality. One of the fundamental problems is that it is difficult to evaluate the results of corporate climate risk assessment. This study constructs the Evaluation of Corporate Climate Risk Assessment Results (ECCRAR) scheme. It analyzes the sustainability reports and TCFD reports of Taiwan’s 100 largest firms by total market capitalization. The findings reveal significant variation in their physical and transition risk assessment performance. Issues identified include inappropriate scenario settings, assessment tools, and sources of information, as well as flawed or unclear risk assessments. Additionally, there is an overly conservative use of assessment tools, with a heavy reliance on free resources and official graphics (such as hazard potential maps and inundation maps), with extremely low use of transition risk assessment tools and graphics. We also recommend increasing the use of fixed-temperature warming scenarios. The research results provide a useful reference to corporate and government decision makers, and also raise the analytical scheme and new empirical cases for further research.